Dampak Pandemi Covid-19 terhadap Pembelajaran Pendidikan Jasmani pada Siswa MA Ghoyatul Jihad Karawang - Fadhlurrahman, Fakhri; Kurniawan, Febi (Universitas Singaperbangsa, 2022)
Coronavirus is a virus that spreads quickly, causing the whole world to experience a health crisis. And Covid-19 has changed various sectors of human life at this time, especially in the world of education. In the education sector, learning is carried out online. Physical education is one of the lessons that are affected by online learning, even though physical education is basically done offline. The purpose of the researcher was to find out how the impact of covid-19 on physical education learning for students in the MA Ghoyatul Jihad education unit Karawang. This type of research uses a qualitative descriptive approach and the subject of students. The research subjects included students by conducting interviews on the implementation of physical education learning during the COVID-19 pandemic. The results of the impact research during the COVID-19 pandemic have changed the implementation of physical education learning at MA Ghoyatul Jihad Karawang into online learning and its implementation has been running effectively according to the objectives.